Brain basis for physical activity levels mediate beta Inhibition to improve cognitive function in elderly based on multimodality monitoring - Zixia Bu; Shan Jiang; Tingting Sun; Zhenxing Yang; Mo Sha; Fuqiang Dong (Scientific Reports)
Abstract The ameliorative effect of regular physical activity (PA) on cognitive function (CF) in older adults has been demonstrated. However, there are differences in the effects of different levels of PA on CF over time. To provide a more efficient exercise prescription for older adults, we compared differences in CF with neural mechanisms in individuals with different weekly activity levels. In this study, 68 older adults (n = 68, M = 47, F = 21, Age = 62.43 ± 4.36) were categorized according to the International Physical Activity Questionnaire (IPAQ) into high volume PA group (HG) (MET-min/week = 1516.64 ± 138.68), moderate volume PA group (MG) (MET-min/week = 1248.02 ± 119.86), and control group (MET-min/week = 1248.02 ± 119.86). 1516.64 ± 138.68), moderate volume PA group (MG) (MET-min/week = 1248.02 ± 119.86), and control group (MET-min/week = 846.78 ± 97.53). Differences in Stop Signal, Stroop, and 2-Back were compared among the three groups. Electroencephalogram (EEG), event-related potential (ERP), and magnetic resonance imaging (MRI) features were also observed. The results showed that for CF, 2-Back with Stroop was significantly higher in MG versus HG than in CG (F = 121.45, P < 0.01; F = 88.74, P < 0.01), and the opposite was true for response (F = 236.83, P < 0.01; F = 187.64, P < 0.01). Stroop was higher in HG than in MG (F = 38.78, P = 0.037) and Stop Signal was higher than in CG (F = 52.03, P < 0.01). In terms of EEG, the alpha band share of HG was higher than CG at rest (F = 41.34, P = 0.040) and the opposite in work (F = 25.67, P = 0.046). Although the remaining results were not statistically significant, PA levels were inversely proportional to resting midrange-band β (CG = 8.98 ± 1.02, MG = 8.07 ± 0.76, HG = 8.13 ± 0.88), and positively proportional to midrange and high-band β in WORK (midrange β: CG = 12.41 ± 2.29, MG = 12.98 ± 3.04, HG = 13.21 ± 2.85; high β: CG = 6.76 ± 2.23, MG = 7.35 ± 1.96, HG = 7.91 ± 2.3). In ERP, the latencies of N200, P300, and N450 were significantly shorter than those of CG in HG (F = 44.63, P = 0.041; F = 29.69, P = 0.045; F = 76.48, P < 0.01), and only N450 was shorter than that of CG in MG (F = 59.62, P < 0.01). On MRI, HG had Middle Frontal Gyrus (MFG) (HG > CG, voxel = 188, t = 3.72), Right Superior Frontal Gyrus (RSFG) (HG > CG, voxel = 238, t = 4.07), Left Cingulate (HG > CG, voxel = 343, t = 4.36), and Left Supplementary Motor Area (LSMA) (HG > CG, voxel = 343, t = 4.36) were activated more than CG. MFG (MG > CG, voxel = 172, t = 3.56), LSMA (MG > CG, voxel = 331, t = 4.28), and PHG (MG > CG, voxel = 204, t = 3.35) were activated more than CG. It was concluded that PA significantly enhanced CF in older adults, and that high volume PA was more effective than moderate volume. Specifically, VPA was found to be significantly more effective than MPA and LPA in enhancing individuals’ inhibition function, cognitive flexibility, working memory, and reaction speed. This may be attributed to the increase in ERP amplitude with shorter latency and greater gray matter density in frontal and temporal lobe regions.